Identidades territoriales - Daniel Nordman (Mélanges de la Casa de Velázquez)
In counterpoint to the other articles published in this dossier, the author proposes a comparativistic approach utilising elements chosen with no systematic intent and based on cases far removed from one another in space and time. From both a historiographic and a critical standpoint, he reviews the question of the age of boundaries (and the long-lasting debate on the subject of their stability), relationships between administrative circumscriptions and feelings of territorial belonging in the France of the Ancien Regime, relationships between language, territory and nation from the Renaissance until the debate between Fustel de Coulanges and Mommsen, and shifts of identity. The latter is far from being essential or natural but on the contrary is subject to composition and recomposition based on changing criteria, as reflected in the evolution of the Bedouins of Cyrenaica according to the research of Peters.